Mapping ground deformation over Houston–Galveston, Texas using multi-temporal InSAR - Qu, Feifei; Lu, Zhong; Zhang, Qin; Bawden, Gerald W.; Kim, Jin-Woo; Zhao, Chaoying; Qu, Wei (Remote sensing of environment, 2015)
Houston–Galveston (HG) region in Texas has been subsiding due to the combined effects of groundwater withdrawal, hydrocarbon extraction, salt dome movement, and faulting. This human- and partially nature-induced ground deformation has gradually threatened the stability of urban infrastructure and caused the loss of wetland habitat along the Gulf of Mexico. Interferometric synthetic aperture radar (InSAR) techniques can measure ground motions in high spatial resolution over large coverage. The purpose of this study is to map the spatial and temporal variations in surface deformation around the HG region using a Multi-Temporal InSAR (MTI) technique and to assess the role of fluid withdrawal (groundwater withdrawal and hydrocarbon extraction), salt tectonics, and fault activity in land surface deformation. MTI-derived land surface deformation measurements are then compared to GPS and extensometer observations, geologic and hydrologic data, and information about hydrocarbon extraction to address the causes of the observed deformation. The MTI measurements based on ERS-1/2 datasets have mapped regional subsidence up to 53mm/yr in the northwestern HG as well as a slight uplift at 20mm/yr in the southeastern HG from 1993 to 2000. InSAR measurements obtained from Envisat and ALOS data reveal subsidence rate of up to 30mm/yr over the northwestern HG between 2004 and 2011. Our results indicate that the pattern of ground deformation was nearly concentric around locations of intense groundwater withdrawal and the spatial extent of the subsiding area has been shrinking and migrating toward the northeast after 2000. We have resolved localized ground subsidence cones over hydrocarbon exploration fields, which were likely caused by reservoir compaction. We have differentiated ground surface deformation over salt domes, which was due to ongoing differential movement of individual salt spines. We have identified 5–40mm/yr differential subsidence across a number of faults in the region. These faults functioned as water barriers disrupting the integrity of ground water flow and aggravating localized surface displacements. •Advanced InSAR unveils spatial–temporal variations of land subsidence over Houston.•Land subsidence correlates with the change in ground water level.•Local subsidence is formed around active hydrocarbon exploration wells.•Ongoing differential movement of salt dome can generate localized subsidence.•Faults function as water barriers to induce localized surface displacement.